PEMANFAATAN LINGKUNGAN OUTDOOR SEBAGAI SUMBER BELAJAR PADA ANAK USIA 5-6 TAHUN DI TK - Mustamiroh, Mustamiroh; Syukri, M.; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbtractThis study aims to describe about planning of the use of outdoor play area and what are the obstacles in learning that using outdoor play area as learning sources done for 5-6 years old preschool children in kindergarten LKIA III Pontianak. The method of research is descriptive study, and using qualitative approach. The techniques used are observation, interview, and documentation. The data collection instruments are interview guideline, observation guideline, documentation study and field note. From the result obtainned that how is the planning on using outdoor play area, managing outdoor play area, children’s respond in using outdoor play area and what are the obstacle factors in learning using outdoor play area as learning source done on 5-6 years old children in TK LKIA III Pontianak Selatan. Keywords : Outdoor Play Area, Learning Source, Children